2019
DOI: 10.1186/s13765-019-0468-7
|View full text |Cite
|
Sign up to set email alerts
|

Antimelanogenic activities of piperlongumine derived from Piper longum on murine B16F10 melanoma cells in vitro and zebrafish embryos in vivo: its molecular mode of depigmenting action

Abstract: In this study, the antimelanogenic activity of piperlongumine in murine B16F10 melanoma cells and zebrafish was investigated, and its mode of antimelanogenic action was elucidated using quantitative reverse transcription-polymerase chain reaction. A melanocyte-stimulating hormone (α-MSH, 200 nM) was used to induce melanin production in B16F10 melanoma cells, and kojic acid (200 μM) was used as a positive control. Piperlongumine had no inhibitory effects on cell growth at the treated concentrations (3 and 6 μM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…For instance, Mustapha et al [ 45 ] showed that both the ethyl acetate leaf extract of Crataegus azarolus L. (12.5 μg/mL) and one of its main constituents, vitexin-2ʺ- O -rhamnoside (5 μM), decreased the production of intracellular melanin in B16F10 cells by threefold as compared to untreated cells. Measuring the melanin content and release in B16F10 cells was also used to prove the anti-melanogenic activity of piperlongumine derived from Piper longum L. [ 48 ]. Piperlongumine (3 and 6 μM) had no inhibitory effects on the cell growth, but it significantly reduced the total melanin production by down-regulating the tyrosinase activity and expression of several pro-melanogenic proteins, such as tyrosinase-related protein-1 (TRP-1), TRP2, and microphthalmia-associated transcription factor (MITF) [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Mustapha et al [ 45 ] showed that both the ethyl acetate leaf extract of Crataegus azarolus L. (12.5 μg/mL) and one of its main constituents, vitexin-2ʺ- O -rhamnoside (5 μM), decreased the production of intracellular melanin in B16F10 cells by threefold as compared to untreated cells. Measuring the melanin content and release in B16F10 cells was also used to prove the anti-melanogenic activity of piperlongumine derived from Piper longum L. [ 48 ]. Piperlongumine (3 and 6 μM) had no inhibitory effects on the cell growth, but it significantly reduced the total melanin production by down-regulating the tyrosinase activity and expression of several pro-melanogenic proteins, such as tyrosinase-related protein-1 (TRP-1), TRP2, and microphthalmia-associated transcription factor (MITF) [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The demand for natural pigment reducers for pharmaceutical and cosmetic applications has increased rapidly [38,39]. Recently, natural products have been considered effective sources of…”
Section: Discussionmentioning
confidence: 99%
“…Although the primary role of melanin is the protection of skin tissue from UV irradiation, age spots and freckles can form as a result of the excessive production of melanin [3][4][5][6][7][8][9][10][11][12][13]. Considerable efforts have been made to develop products that reduce melanin synthesis for use as whitening constituents [23,29,[36][37][38][39][40][41][42]. TYR is an oxidase and is the rate-limiting enzyme in the production of melanin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations